Mandatory vaccination for healthcare workers: an ethical dilemma?. (2nd March 2022) - Tang, Sammer; Stanley, Jake; Campbell, Iain
Abstract : Vaccines are advocated as the best defence against COVID-19. While most NHS staff, including ambulance clinicians, have been vaccinated, some remain hesitant. All health and social care staff, with some exemptions, were originally expected to be fully vaccinated by 1 April 2022. However, this is currently on hold due to the recent reconsideration by the Secretary of State. There are ethical arguments against and in favour of mandatory vaccination. Arguments against include potential harm and loss of autonomy. Coercing staff may be interpreted by the public that health professionals do not trust vaccines. A mandate may also be seen as authoritarian, which may embolden the anti-vaccine movement. Compulsory vaccination is also opposed by Royal Colleges, professional bodies and trade unions. Arguments to support mandatory vaccination include that society has a legitimate interest in regulating behaviour that harms others, even if this limits individual choices and that people live in groups so their rights and powers are limited by the rights of others. Paramedics deal with a diverse population, and often encounter clinically vulnerable patients as well as those who are COVID-19 positive. It can be argued that patients' right to be safe from unnecessary risk usurps that of a practitioner to refuse vaccination. Having all health and social care staff fully vaccinated will increase the health service's resilience. Future decisions on any vaccine mandates must incorporate various ethical arguments and support with additional effort to address underlying issues related to vaccine hesitancy.